Grass Growth and N2O Emissions From Soil After Application of Jellyfish in Coastal Areas - Borchert, Florian; Emadodin, Iraj; Kluß, Christof; Rotter, Ana; Reinsch, Thorsten (Frontiers in Marine Science, 2021)
The supply of nutrients for agricultural production faces enormous challenges as food security and sustainability goals have to be ensured. Processing of marine biomass has high potential to provide nutrients for agricultural purposes in coastal areas. One underexplored resource is jellyfish, which occur as blooms and by-catch of the fishing industry. In this context, a pot experiment investigated the effects of jellyfish as a fertilizer on biomass accumulation of annual ryegrass (Lolium multiflorum), and its effect on the important greenhouse gas N2O as a sustainability indicator of novel fertilizers. Dried and ground jellyfish was applied (3 species: Aurelia aurita (AA), Cyanea capillata (CC), Periphylla periphylla (PP)) and compared with an unfertilized and a mineral fertilized (calcium-ammonium-nitrate, CAN) treatment. Dried jellyfish and CAN were applied at equal N rates of 5 g N per m2. The N2O-fluxes from soil were measured over 56 days after fertilizer application. Grass dry matter yields, when using CC and PP treatments, were not significantly different to the CAN treatment (p>0.05). After reducing its salinity, AA also showed no differences to CAN on plant growth and the lowest coefficient of variation for dry matter yield as an indicator for yield stability. Accumulated N2O-emissions were lowest in the control and were 3-times higher in AA and CC compared to CAN (p<0.05). If salinity levels are moderate, jellyfish application to soil can compete with artificial mineral fertilizers in terms of N-supply for above- and belowground yield response, regardless of jellyfish species used. However, elevated N2O-emissions are likely to affect its suitability for large-scale application. Nevertheless, if energy-efficient methods of drying and desalination of jellyfish can be developed, in coastal areas dried jellyfish is a valuable fertilizer particularly in situations where nutrient supplies for agriculture are limited.